Assessment of Parafunctional Habits Among South Indian Population: A Retrospective Institutional Study - KAMDAR, RUSHABH; RAMAKRISHNAN, MAHESH; M, ARUN (The journal of contemporary issues in business and government, 2020)
Parafunctional habits are any abnormal behaviour or functioning of the oral structures and associated muscles. Abnormal behaviour commonly includes bruxism, thumb-sucking, breathing disorder and lip biting. The aim of the study was to assess parafunctional oral habits like tongue thrusting, mouth breathing and thumb-sucking among the South Indian population. Completed case sheets were collected from patients reported to a private Dental Hospital, India during the time frame from June 2019 to March 2020. Data was retrieved and evaluated by 2 reviewers. In this study, more children were associated with parafunctional habits between the age group 5-9 compared to children in the age group of 10-14 years. Parafunctional habits were found to be gender related. The Incidence of these habits were found to be more in boys than in girls, but not statistically significant correlation. Parafunctional habits like lip biting, tongue thrusting and thumb-sucking were found to be associated more in the age group of 5-9yrs old. Fixed appliances are the preferred treatment option when compared to removable appliances.